Therapeutic Potential of a Self-Assembling Peptide Hydrogel to Treat Colonic Injuries Associated with Inflammatory Bowel Disease. (17th February 2021) - Araki, Toshihiro; Mitsuyama, Keiichi; Yamasaki, Hiroshi; Morita, Masaru; Tsuruta, Kozo; Mori, Atsushi; Yoshimura, Tetsuhiro; Fukunaga, Shuhei; Kuwaki, Kotaro; Yoshioka, Shinichiro; Takedatsu, Hidetoshi; Kakuma, Tatsuyuki; et al.
Abstract: Background and Aims: The Self-assembling Peptide Hydrogel [SAPH, PuraMatrix], a fully synthetic peptide solution designed to replace collagen, has recently been used to promote mucosal regeneration in iatrogenic ulcers following endoscopic submucosal dissection. Herein, we evaluated its utility in ulcer repair using a rat model of topical trinitrobenzene sulphonic acid [TNBS]-induced colonic injuries. Methods: Colonic injuries were generated in 7-week-old rats by injecting an ethanol solution [35%, 0.2 mL] containing 0.15 M TNBS into the colonic lumen. At 2 and 4 days post-injury, the rats were subjected to endoscopy, and SAPH [or vehicle] was topically applied to the ulcerative lesion. Time-of-flight secondary ion mass spectrometry [TOF-SIMS] was used to detect SAPH. Colonic expression of cytokines and wound healing-related factors were assessed using real-time polymerase chain reaction or immunohistochemistry. Results: SAPH treatment significantly reduced ulcer length [ p  = 0.0014] and area [ p  = 0.045], while decreasing colonic weight [ p  = 0.0375] and histological score [ p  = 0.0005] 7 days after injury. SAPH treatment also decreased colonic expression of interleukin [ IL ] -1α [ p  = 0.0233] and IL-6 [ p  = 0.0343] and increased that of claudin-1 [ p  = 0.0486] and villin [ p  = 0.0183], and β-catenin staining [ p  = 0.0237]. TOF-SIMS revealed lesional retention of SAPH on day 7 post-injury. Furthermore, SAPH significantly promoted healing in in vivo mechanical intestinal wound models. Conclusions: SAPH application effectively suppressed colonic injury, downregulated inflammatory cytokine expression, and upregulated wound healing-related factor expression in the rat model; thus, it may represent a promising therapeutic strategy for IBD-related colonic ulcers.